2019
DOI: 10.3390/jcm8060856
|View full text |Cite
|
Sign up to set email alerts
|

Safety Evaluation of Tadalafil Treatment for Fetuses with Early-Onset Growth Restriction (TADAFER): Results from the Phase II Trial

Abstract: Tadalafil is a phosphodiesterase 5 (PDE5) inhibitor with a long half-life, high selectivity, and rapid onset of action. Because the safety of using PDE5 inhibitors as therapeutic agents for fetal growth restriction (FGR) has been a problem worldwide, this paper primarily focuses on the safety assessments performed in the Tadalafil Treatment for Fetuses with Early-Onset Growth Restriction (TADAFER) II population. Neonatal and maternal adverse events were analyzed, in addition to fetal, neonatal, and infant deat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(55 citation statements)
references
References 29 publications
0
55
0
Order By: Relevance
“…There were no severe fetal and neonatal adverse events that seemed to be related to tadalafil. Adverse events were expressed by grade based on the Common Terminology Criteria for Adverse Events v4.0, as with the TADAFER II study [11].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were no severe fetal and neonatal adverse events that seemed to be related to tadalafil. Adverse events were expressed by grade based on the Common Terminology Criteria for Adverse Events v4.0, as with the TADAFER II study [11].…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the TADAFER II study revealed that tadalafil administration prolonged gestation, in contrast to the STRIDER study [10]. Sildenafil, as a PDE5 inhibitor, did not prolong gestation in FGR in the STRIDER study [11,12]. The differences between the STRIDER study and the TADAFER study are shown in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we report, for the first time, a developmental evaluation of infants who had received tadalafil in utero as a novel therapeutic treatment for FGR. Although the TADAFER II trial was suspended without completing registration of the original planned number of cases, the study concluded (as a short-term prognosis) that fetal, neonatal, and infant deaths decreased, and that this observation was potentially due to the prolongation of the gestational period in the case of early-onset FGR [1].…”
Section: Discussionmentioning
confidence: 99%
“…Tadalafil, a phosphodiesterase 5 (PDE5) inhibitor, has been reported to be a potential drug for the treatment of FGR. The results of a phase II trial (TADAFER II) using tadalafil for the treatment of fetuses with early-onset growth restriction have already been published [1]. Although the Japan Agency for Medical Research and Development (AMED) recommended suspension of TADAFER II based on the results of the STRIDER-UK trial showing negative effects of sildenafil in the treatment of FGR [2] and the recruitment of new candidates for the trial was ceased, the study demonstrated a decrease in the mortality rate of FGR fetuses, neonates, and infants.…”
Section: Introductionmentioning
confidence: 99%
“…Written informed consent was obtained from a Japanese pregnant woman. The placental sample in FGR and FGR + tadalafil cases used case in clinical trial [ 19 ]. Control case selected randomly the normal case during clinical trial.…”
Section: Methodsmentioning
confidence: 99%